How do pharmacists select antimicrobials? A model of pharmacists' therapeutic reasoning processes. Issue 4 (30th December 2021) - Gruenberg, Katherine; Abdoler, Emily; O'Brien, Bridget C.; Schwartz, Brian S.; MacDougall, Conan
Abstract: INTRODUCTION: Clinicians engage in clinical reasoning, comprised of both diagnostic and therapeutic components, when caring for patients. While diagnostic reasoning has been extensively investigated, relatively few studies have examined how clinicians make treatment decisions. Recent work has explored how physicians engage in therapeutic reasoning while selecting antimicrobials. However, understanding pharmacists' antimicrobial reasoning is equally important due to their role in ensuring appropriate antimicrobial use. Therefore, we aimed to further our understanding of antimicrobial reasoning in pharmacists and compare their reasoning processes to physicians. METHODS: With a postpositivist orientation and using a general qualitative approach, we conducted semi‐structured interviews with hospital‐based pharmacists specializing in infectious diseases or other hospital‐based specialties. Participants narrated their thought processes while selecting antimicrobials for three case vignettes. We analyzed transcripts iteratively using a code book from a prior study of antimicrobial reasoning in physicians as a sensitizing framework. RESULTS: Participants included 11 pharmacists (5 infectious diseases and 6 noninfectious diseases pharmacists). Overall, participants' responses reflected a three‐step reasoning process: Naming the Syndrome, Delineating Pathogens, and Selecting the Antimicrobial . Patient‐, syndrome‐, and system‐based factors interacted with drug characteristics to influence the selection of specific antimicrobial regimens. CONCLUSION: We identified a framework for pharmacists' antimicrobial therapeutic reasoning similar to physicians' reasoning, with some nuances that may be attributable to the pharmacists' role in medication review and antimicrobial stewardship. Application of this framework has the potential to aid in teaching, improve multidisciplinary care, and provide a framework for interprofessional communication.